Correlating morphology and doping effects with the carbon monoxide catalytic activity of Zn doped CeO2 nanocrystals. Issue 1 (15th December 2017) - Du, Haiwei; Wang, Yuan; Arandiyan, Hamidreza; Scott, Jason; Wan, Tao; Chu, Dewei
Abstract : The morphology-dependent doping effects on CeO2 nanocrystals were investigated for the catalytic oxidation of carbon monoxide (CO). Abstract : The effects of Zn-doping on CeO2 nanocrystals were investigated for the catalytic oxidation of carbon monoxide (CO). Incorporating Zn 2+ into CeO2 nanocubes with an isotropic 3D structure can effectively regulate oxygen vacancy concentration, compared with CeO2 nanorods showing an anisotropic one dimensional 1D structure. The catalytic activity was shown to be governed by a morphology-dependent doping effect.